2015
DOI: 10.3389/fpsyg.2015.00475
|View full text |Cite
|
Sign up to set email alerts
|

Musical training as an alternative and effective method for neuro-education and neuro-rehabilitation

Abstract: In the last decade, important advances in the field of cognitive science, psychology, and neuroscience have largely contributed to improve our knowledge on brain functioning. More recently, a line of research has been developed that aims at using musical training and practice as alternative tools for boosting specific perceptual, motor, cognitive, and emotional skills both in healthy population and in neurologic patients. These findings are of great hope for a better treatment of language-based learning disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 222 publications
6
41
0
5
Order By: Relevance
“…Additionally, although there were no differences between groups at the cognitive level, the within‐groups analyses showed that the MST group improved their attention and verbal memory after the training. Similar findings have been previously described at the cognitive and emotional levels after MST in chronic stroke patients, as well as in other music programs for neurological population . Thus, these results reinforce the capacity of music in therapeutic programs as a mood enhancer…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, although there were no differences between groups at the cognitive level, the within‐groups analyses showed that the MST group improved their attention and verbal memory after the training. Similar findings have been previously described at the cognitive and emotional levels after MST in chronic stroke patients, as well as in other music programs for neurological population . Thus, these results reinforce the capacity of music in therapeutic programs as a mood enhancer…”
Section: Discussionsupporting
confidence: 89%
“…In these sessions, a wide range of techniques are used, although a recent meta‐analysis only supported the use of modified constraint‐induced movement therapy and task‐specific training in the first 4 weeks poststroke . In addition, other emerging evidence‐based techniques could be introduced into the rehabilitation programs as add‐on treatments to boost the recovery of stroke patients . These techniques are designed to improve not only motor deficits but also other relevant aspects, including motivation, treatment adherence, and mood, all of which are known to contribute to the success of the rehabilitation process .…”
Section: Introductionmentioning
confidence: 99%
“…Music engages multiple facets of the human experience, tapping into sensory, motor, cognitive, and emotional domains, as a few examples. Several literature reviews have provided thorough discussion on the role of these factors in enhancing stroke motor recovery . I will not repeat these ideas here, except to say that these factors, or hypothesized active ingredients, can be categorized into two broad themes.…”
Section: Music Supported Therapy (Mst) For Motor Recoverymentioning
confidence: 99%
“…The study of music‐based therapies on motor recovery after stroke may be broadly categorized into two approaches: those that test the role of RAS, and those that evaluate the role of making music. I refer the reader to several literature reviews that have evaluated and discussed the results of these studies . Thus, I will not repeat what has already been synthesized, but instead provide a discussion about the results of these studies in the context of recent systematic reviews with meta‐analyses …”
Section: Music Supported Therapy (Mst) For Motor Recoverymentioning
confidence: 99%
“…Nesta proposta de intervenção emprega-se um ritmo confortável como estimulação auditiva rítmica para adequar os parâmetros espaço-temporais da marcha. Sendo assim, esta conexão entre ritmo e parâmetros da marcha pode justificar o uso clínico da estimulação auditiva rítmica nos processos de reabilitação da marcha em pacientes com doenças neurológicas 12 .…”
Section: Introductionunclassified